Brain as agent and conscious mind as action guide: From Libet-style experiments to necessary conditions for free will - Coelho, Jonas Gonçalves [UNESP] (UNISINOS - Universidade do Vale do Rio Dos Sinos, 2021)
Many neuroscientific experiments, based on monitoring brain activity, suggest that it is possible to predict the conscious intention/choice/decision of an agent before he himself knows that. Some neuroscientists and philosophers interpret the results of these experiments as showing that free will is an illusion, since it is the brain and not the conscious mind that intends/chooses/decides. Assuming that the methods and results of these experiments are reliable the question is if they really show that free will is an illusion. To address this problem, I argue that first it is needed to answer three questions related to the relationship between conscious mind and brain: 1. Do brain events cause conscious events? 2. Do conscious events cause brain events? 3. Who is the agent, that is, who consciously intends/chooses/ decides, the conscious mind, the brain, or both? I answer these questions by arguing that the conscious mind is a property of the brain due to which the brain has the causal capacity to interact adaptively with its body, and trough the body, with the physical and sociocultural environment. In other words, the brain is the agent and the conscious mind, in its various forms - cognitive, volitional and emotional - and contents, is its guide of action. Based on this general view I argue that the experiments aforementioned do not show that free will is an illusion, and as a starting point for examining this problem I point out, from some exemplary situations, what I believe to be some of the necessary conditions for free will.
Cérebro como agente e mente consciente como guia de ação: Experimentos estilo-Libet e as condições necessárias para o livre-arbítrio
Keywords: Agent brain; Conscious mind; Free will; Libet-style experiments